44
$\begingroup$

This is a question from Math Olympiad.

If $\{x,y,z\}\subset\Bbb{R}^+$ and if $$x^2 + xy + y^2 = 3 \\ y^2 + yz + z^2 = 1 \\ x^2 + xz + z^2 = 4$$ find the value of $xy+yz+zx$.

I basically do not know how to approach this question. Please let me know how to approach this question, and if you attach full explanation, I will appreciate it. Thanks.

$\endgroup$
5
  • 11
    $\begingroup$ Could you provide some background about methods you’ve tried that have failed and about your mathematical skillset? $\endgroup$ Feb 9, 2018 at 13:44
  • 1
    $\begingroup$ Wouldn't this be solving multiple equations with multiple unknowns? $\endgroup$ Feb 9, 2018 at 15:02
  • 1
    $\begingroup$ If all else failed, I would personally try finding a Groebner basis of the corresponding ideal, and then if that doesn't directly give $x,y,z$, hopefully at least dividing $xy+yz+zx$ by the ideal would give a constant remainder. (Keeping my fingers crossed that the problem would also be solvable for $x,y,z \in \mathbb{C}$ and doesn't on the contrary require using some inequalities.) $\endgroup$ Feb 9, 2018 at 20:16
  • 1
    $\begingroup$ I added an answer with the Gröbner basis idea (before seeing your comment). It does involve using the inequality at some point, but it remains clean, fortunately ! $\endgroup$
    – Antoine
    Feb 9, 2018 at 20:38
  • 1
    $\begingroup$ My gut feeling (also because it is a quiz for young adults) is that there is some clever way to exploit the symmetry of the equations without going the whole 9 yards. $\endgroup$ Feb 12, 2018 at 11:06

6 Answers 6

74
$\begingroup$

We can obtain $yz+zx+xy=2$ simply by finding the values of $x$, $y$, and $z$. We are given $$y^2+yz+z^2=1,\qquad(1)$$$$z^2+zx+x^2=4,\qquad(2)$$$$x^2+xy+y^2=3,\,\qquad(3)$$with $x,y,z>0$. Subtracting eqn $3$ from eqn $2$, and noticing the factor $z-y$ on the LHS, gives $$(z-y)(x+y+z)=1.$$Similarly, from eqn $2$ minus eqn $1$, we get$$(x-y)(x+y+z)=3.$$The ratio of the latter two equations yields $x-y=3(z-y)$, or$$x=3z-2y.$$ Now substituting for $x$ from the above equation into eqn $3$ yields$$y^2-3yz+3z^2=1.$$By subtracting this from eqn $1$, we find $2yz-z^2=0$, or$$z=2y$$(since $z\neq0$). Substitution for $z$ into eqn $1$ now gives $7y^2=1$. It follows that $y=1/\surd7$, because $y>0$, and then $z=2/\surd7$ and $x=4/\surd7$, giving$$yz+zx+xy=2.$$

$\endgroup$
3
  • 1
    $\begingroup$ Nice and straightforward, no magic involved. Gets my vote! $\endgroup$
    – Noldorin
    Feb 10, 2018 at 3:26
  • 14
    $\begingroup$ I like this solution especially because I hate geometry. $\endgroup$
    – actinidia
    Feb 10, 2018 at 6:05
  • $\begingroup$ Precisely my solution, +1. $\endgroup$
    – Ennar
    Feb 11, 2018 at 20:39
53
$\begingroup$

To my surprise, this problem can be solved using geometry.

Identify the Euclidean plane with complex plane $\mathbb{C}$. and let $\omega = e^{\frac{2\pi}{3}i}$ be the cubic root of unity.

Consider triangle $\triangle ABC$ with vertices at $A = x$, $B = y\omega$ and $C = z\omega^2$.
The sides of the triangle equal to

$$\begin{align} a^2 = BC^2 &= | y\omega - z\omega^2|^2 = y^2 + yz+ z^2 = 1\\ b^2 = AC^2 &= | x - z\omega^2|^2 = x^2 + xz + z^2 = 4\\ c^2 = AB^2 &= | x - y\omega|^2 = x^2+xy+y^2 = 3 \end{align} $$ Since $a^2 + c^2 = b^2$, this is a right angled triangle with area $\mathcal{A} = \frac12 ac =\frac{\sqrt{3}}{2}$.

An alternate way to compute the area is cut the triangle into 3 pieces along the line $OA$, $OB$ and $OC$. This gives us

$$\mathcal{A}= \frac12 (xy + yz + xz)\sin\frac{2\pi}{3} = \frac{\sqrt{3}}{4} (xy+yz+xz)$$ Combine these two results, we find: $$xy+yz+xz = 2$$

Update

For a pure algebraic answer, one can substitute above expression of $a^2,b^2,c^2$ into Heron's formula for area of triangle, $$\mathcal{A} = \frac14\sqrt{(a^2+b^2+c^2)^2-2(a^4+b^4+c^4)}$$ simplify and obtain following algebraic identity

$$\begin{array}{rl} 3(xy+yz+zx)^2 =& \phantom{+0}((x^2+xz+y^2) + (y^2+yz+z^2) + (z^2+xz+x^2))^2\\ &-2((x^2+xz+y^2)^2 + (y^2+yz+z^2)^2 + (z^2+xz+x^2)^2) \end{array} $$ Using given values of $a, b, c$, we find $$3(xy+yz+xz)^2 = (3+4+1)^2 - 2(3^2+4^2+1^2) = 64 -2(26) = 12 = 3(2)^2$$ This leads to the same conclusion $xy+yz+xz = 2$ as before.

$\endgroup$
4
  • 1
    $\begingroup$ It is precisely from a geometric construction that I get the below inequality! $\endgroup$
    – user284001
    Feb 9, 2018 at 12:27
  • $\begingroup$ It also implies that $x^2 + y^2 + z^3$ is equal to $3$, right? $\endgroup$ Feb 9, 2018 at 14:07
  • 1
    $\begingroup$ @EricDuminil yes, if you mean $x^2+y^2+z^2 = 3$. $\endgroup$ Feb 9, 2018 at 14:17
  • $\begingroup$ @achillehui: Yes, that was a typo. $\endgroup$ Feb 9, 2018 at 14:27
18
$\begingroup$

I would like to mention an other method, more algorithmic but also much more general to this problem.

First compute a Gröbner basis (say, using the lexicographic order) of the three polynomials $$x^2 + xy + y^2 - 3 \\ y^2 + yz + z^2 - 1 \\ x^2 + xz + z^2 - 4$$ One obtains $\left\{7 z^3-4 z,2 y z-z^2,2 y^2+3 z^2-2,x+2 y-3 z\right\}$.

We want to evaluate $xy+yz+zx$, which is presumably a constant, under the given conditions. This means that $xy+yz+zx-a$ belongs to the ideal generated by the three above polynomials, for some constant $a$ to be determined. Let's evaluate the remainder of the Euclidean division of $xy+yz+zx-a$ by the Gröbner basis given above: one finds $$-2-a+7z^2 \, . $$ This should be zero, if our relation is to be a consequence of the original relations. So we deduce $a=7z^2-2$.

What is the value of $z^2$? Well, the first term of the Gröbner basis tells us that $z(7z^2-4)=0$, so $z^2 = 0 , 4/7$, and therefore $a= \pm 2$.

To fix the sign, we need the last piece of information, namely that $x,y,z \geq 0$. Clearly, if $z=0$ then the last term of the basis tells us that $x+2y=0$, which is forbidden (since $x=y=z=0$ is not a solution). Therefore, $z^2 = 4/7$ and $a=2$.

$\endgroup$
16
$\begingroup$

Suppose $x,y,z > 0$ satisfy the system $$ \begin{cases} x^2 + xy + y^2 = 3&\;\;\;(\text{eq}1)\\[4pt] y^2 + yz + z^2 = 1&\;\;\;(\text{eq}2)\\[4pt] z^2 + zx + x^2 = 4&\;\;\;(\text{eq}3)\\ \end{cases} $$ From $(\text{eq}2)$, since $y,z > 0$, we get $y,z < 1$, hence from $(\text{eq}1)$, we must have $x > 1$.

Let $a = x + y + z$, and let $b = xy + yz + zx$.

The goal is to find the value of $b$.

Since $x,y,z > 0$, and $x > 1$, we get $a > 1$.

Identically, we have $x^2 + y^2 + z^2 = a^2 -2b$.

From the sum $(\text{eq}1)+ (\text{eq}2) +(\text{eq}3)$, we get $$2(x^2 + y^2 + z^2) + (xy + yz + zx) = 8$$ hence $$2a^2-3b=8\qquad(\text{eq}4)$$

Subtracting $(\text{eq}2)$ from $(\text{eq}1)$, we get \begin{align*} &(x^2 +xy + y^2) - (y^2 + yz + z^2) = 2\\[4pt] \implies\;&(x^2 - z^2) + (xy - yz) = 2\\[4pt] \implies\;&(x-z)(x+y+z) = 2\\[4pt] \implies\;&x-z =\frac{2}{a}\\[4pt] \implies\;&z^2-2zx+x^2 = \frac{4}{a^2}\qquad(\text{eq}5)\\[4pt] \end{align*} Subtracting $(\text{eq}2)$ from $(\text{eq}3)$, we get \begin{align*} &(z^2 +zx + x^2) - (y^2 + yz + z^2) = 3\\[4pt] \implies\;&(x^2 - y^2) + (zx - yz) = 3\\[4pt] \implies\;&(x-y)(x+y+z) = 3\\[4pt] \implies\;&x-y =\frac{3}{a}\\[4pt] \implies\;&x^2-2xy+y^2 = \frac{9}{a^2}\qquad(\text{eq}6)\\[4pt] \end{align*} Subtracting $(\text{eq}1)$ from $(\text{eq}3)$, we get \begin{align*} &(z^2 +zx + x^2) - (x^2 + xy + y^2) = 1\\[4pt] \implies\;&(z^2 - y^2) + (zx - xy) = 1\\[4pt] \implies\;&(z-y)(x+y+z) = 1\\[4pt] \implies\;&z-y =\frac{1}{a}\\[4pt] \implies\;&y^2-2yz+z^2 = \frac{1}{a^2}\qquad(\text{eq}7)\\[4pt] \end{align*}

From the sum $(\text{eq}5)+ (\text{eq}6) +(\text{eq}7)$, we get $$2(x^2 + y^2 + z^2) - 2(xy + yz + zx) = \frac{14}{a^2}$$ hence $$a^2-3b=\frac{7}{a^2}\qquad(\text{eq}8)$$ Subtracting $(\text{eq}8)$ from $(\text{eq}4)$, we get \begin{align*} &(2a^2-3b) - (a^2-3b) = 8-\frac{7}{a^2}\\[4pt] \implies\;&a^2 = 8-\frac{7}{a^2}\\[4pt] \implies\;&a^4 - 8a^2 + 7=0\\[4pt] \implies\;&(a^2-1)(a^2-7)=0\\[4pt] \implies\;&a^2 = 7\qquad\text{[since $a > 1$]}\\[4pt] \end{align*} Then from $(\text{eq}4)$, we have $$b = \frac{2a^2-8}{3}$$ hence $$b = \frac{2(7)-8}{3} = 2$$

$\endgroup$
16
$\begingroup$

The given equations $(1),(2),(3)$ can be expressed as: $$\begin{cases} x^3-y^3=3(x-y) \\ y^3-z^3=y-z \\ z^3-x^3=4(z-x)\end{cases} \stackrel{+}{\Rightarrow} x=3z-2y \ \ (4)$$ Plug $(4)$ in $(1)$ and consider it with $(2)$: $$\begin{cases} 3z^2-3zy+y^2=1 \\ y^2+yz+z^2=1\end{cases} \Rightarrow 2z^2-4zy=0 \Rightarrow z=2y \ \ (5)$$ Put $(5)$ to $(4)$ to find $x=4y$. Now you can put $z=2y$ and $x=4y$ to $(1)$ to find $y=\frac{1}{\sqrt{7}}$. Hence: $$xy+yz+zx=\frac{4}{7}+\frac{2}{7}+\frac{8}{7}=2.$$

$\endgroup$
5
$\begingroup$

Possible Hint:

For $x, y, z \in \mathbb{R}^{+}$ $$(x+y+z)^2(yz+zx+xy)^2 \leq 3(x^2+xy+y^2)(y^2+yz+z^2)(z^2+zx+x^2)$$

$\endgroup$
1
  • $\begingroup$ For a proof of this inequality, see here or the linked questions. $\endgroup$
    – Arnaud D.
    Sep 2, 2020 at 11:47

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.